Legislar para prevenir: Seguridad y salud en el teletrabajo post Covid-19 - Espinoza Escobar, Javier H.; Estremadoyro Amaya, Renato (Pontificia Universidad Católica del Perú, 2023)
This article focuses on the importance that teleworking will acquire in the post COVID-19 labor reality in Peru. The pandemic revealed a series of legislative shortcomings linked, among other issues, to those related to the safety and health of teleworkers. For this reason, this article proposes the minimum content that should be incorporated by the Peruvian legislation on teleworking must incorporate in order to guarantee the safety and health of teleworkers. In the construction of said minimum content, international experiences on the subject have been taken into account.

El presente artículo incide en la importancia que el teletrabajo irá adquiriendo en la realidad laboral post COVID-19 en el Perú. La pandemia dejó en evidencia una serie de carencias legislativas vinculadas, entre otras cuestiones, a las relacionadas con la seguridad y salud de los teletrabajadores. Por esa razón, en el presente artículo se propone el contenido mínimo que la legislación peruana sobre teletrabajo debe incorporar a fin de garantizar la seguridad y salud de los teletrabajadores. En la construcción de dicho contenido mínimo se ha tomado en cuenta las experiencias normativas internacionales sobre el particular.
Legislate to prevent: Safety and health in telework post Covid-19
Keywords: Telework; Safety and health at work; Occupational risks; Prevention; Labor law; Teletrabajo; Seguridad y salud en el trabajo; Riesgos laborales; Prevención; Derecho laboral; https://purl.org/pe-repo/ocde/ford#5.05.00